Examining prison rule violations among incarcerated veterans with a history of brain injury, alcohol, and substance use - Chintakrindi, Sriram (Array, 2021)
Background: To investigate how the independent variables: veteran status, brain injury, drug use, and alcohol use predict risk for rule violations and assaulting jail or prison staff while incarcerated. This study used aggregated and disaggregated data to demonstrate relationships between exposure and outcomes. Methods: Cross-sectional survey data was collected from the Survey of Inmates in State and Federal Correctional Facilities (SISFCF), 2004 (n = 14499). Chi-square, Cochran-Mantel-Haenszel (CMH), and logistic regression were conducted to determine the relative contribution of the independent variables in predicting rule violations and assaulting jail or prison staff while incarcerated. The research study tested a number of hypotheses that are listed in the hypotheses section of the research study. Results: The findings from the logistic regression conducted in this study demonstrate a significant relationship between veteran status, alcohol use, and brain injury status and the dependent variable: found guilty or written up for jail or prison rule violations while incarcerated. Conclusion: Alcohol use and brain injury present serious risks for maintaining public health and safety of incarcerated veterans and non-veterans. Daily or almost daily consumption of alcohol was the strongest predictor of jail or prison rule violations. Therefore, researchers and practitioners should continue to develop interventions and policies for reducing alcohol consumption of individuals in contact with the criminal justice system.